Pengaruh Senam Nifas Terhadap Tinggi Fundus Uteri (TFU) Ibu Nifas di Praktek Bidan Mandiri Bd. Sabar Mulianta Sitepu S.Tr.Keb Kecamatan Stabat: Penelitian - Yulida Effendi; Rauda; Delvi Herdina (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The height of the uterine fundus (TFU) is one of the important indicators in assessing the process of uterine involution in the puerperium. Puerperal Gymnastics aims to help accelerate the decline of TFU so as to reduce the risk of complications such as postpartum haemorrhage. This study aims to determine the effect of puerperal Gymnastics on the decrease in tfu in puerperal mothers At Pbm Bd. Sabar Mulianta Sitepu, S.Tr.Keb Stabat District In 2025. The research type is a quasi-experimental pre-test and post-test with one group design. A sample of 10 puerperal mothers was selected using purposive sampling technique based on certain inclusion criteria. The puerperal Gymnastics intervention was administered 1 time per day for 7 consecutive days, and uterine fundus (TFU) measurements were taken before and after the intervention using measuring tapes and observation sheets. Data analysis was conducted using Paired Sample T-Test because the data is normally distributed based on Shapiro-Wilk test. The results showed that the average height of the uterine fundus before puerperal Gymnastics was 4.4 cm, and after puerperal Gymnastics for 7 consecutive days decreased to 2.4 cm. Sample T-Test obtained a value of p = 0.001 (p < 0.05) which means there is a significant difference between before and after the intervention of puerperal.